(untitled) (International Journal of Engineering and Computer Science, 2013)
-Reversible data hiding a novel technique which is used to embed additional information in the encrypted images, applies in military and medical images, which can be recoverable with original media and the hided data without loss. A number of reversible data hiding techniques were proposed in the recent years, but on analysis, all lacks in providing the security and authentication. This project proposes a novel reversible data hiding technique which work is separable, the receiver can extract the original image or extra embedded data or both according to the keys hold by the receiver. On the other hand the receiver can verify the data hided by the data hider, such that the work proposes both security and authentication. This project proposes a novel reversible data hiding technique which poses both security and authentication for additional data stored in the encrypted images. Also proposed work is separable, the receiver can extract the original image or extra embedded data or both according to the keys hold by the receiver. On the other hand the receiver can verify the data hided by the data hider, such that the work proposes both security and authentication. This work proposes a novel scheme for separable reversible data hiding in encrypted images. In the first phase, a content owner encrypts the original uncompressed image using an encryption key. Then, a data-hider may compress the least significant bits of the encrypted image using a data-hiding key to create a sparse space to accommodate some additional data. With an encrypted image containing additional data, if a receiver has the data-hiding key, he can extract the additional data though he does not know the image content. If the receiver has the encryption key, he can decrypt the received data to obtain an image similar to the original one, but cannot extract the additional data. If the receiver has both the data-hiding key and the encryption key, he can extract the additional data and recover the original content without any error by exploiting the spatial correlation in natural image when the amount of additional data is not too larg